Comparison of compound trabeculectomy for angle-closure and open angle glaucoma - Hai-Juan Xie (Guoji Yanke Zazhi, 2016)
AIM: To compared therapeutic effect of compound trabeculectomy in treatment of angle-closure and open angle glaucoma. METHODS: A total of 136 patients(136 eyes)with glaucoma from July 2014 to July 2015 were divided into angle-closure glaucoma(ACG)group with 72 cases(72 eyes)and open angle glaucoma(OAG)group with 64 cases(64 eyes). All the patients were given compound trabeculectomy. The intraocular pressure, shallow anterior chamber, functional follicular and complications were compared between two groups after operation. RESULTS: The intraocular pressure of all patients were significantly decreased at 1 and 3mo after surgery. The intraocular pressure of ACG group were significantly lower than that of OAG group(t=11.037, 12.660, P<0.05). The intraocular pressure control rate of ACG group(98.6%)was significantly higher than that of OAG group(89.1%)(χ2=5.580, P<0.05)at 3mo after surgery. The shallow anterior chamber total incidence of ACG group was 11.1%. It was significantly lower than OAG group(25.0%)(χ2=4.497, P<0.05). The functional follicular formation rate of ACG group was 62.5%. It was significantly higher than OAG group(43.5%)(χ2=4.035, P<0.05). There were no statistically significant on complications between two groups(5.6% vs 7.8%, P=0.475). CONCLUSION: Compound trabeculectomy can reduce intraocular pressure of ACG and OAG patients safely. The results in ACG patients is better than that in OAG patients.